Просторовий аналіз природно-заповідного фонду Закарпатської області - Чубрей, Олександра; Яворська, В; Чир, Н; Мельник, А; Григор'єв, О (JOURNAL OF GEOLOGY, GEOGRAPHY AND GEOECOLOG, 2021)
The article brings light to the study of the nature reserve fund (NRF) of Zakarpatska oblast as a component of the national heritage of the country. Representativeness is considered to be one of the main principles of spatial formation of the NRF object network. Therefore, to determine the current state and ensure further effective development of the region’s nature reserve fund, it is necessary to analyze its territorial and internal structural indicators. The purpose of the study is to analyze the current status of the region’s nature reserve fund with the reference to the possibility of introduction of the further new management practices. The article is based on information and statistical materials, the provisions of regional programs for the formation of the ecological network and environmental legislation of Ukraine. To solve the assigned tasks, there has been done a comprehensive analysis of statistical reporting data and materials of the NRF Register in Zakarpatska oblast of the Department of Ecology of Natural Resources of Zakarpattia Regional State Administration within the period of 2019, and reporting documents of environmental institutions for the same period. The considered indicator is the territorial distribution of nature reserve areas and region areas by administrative districts (before the formation and implementation of changes to the administrative-territorial structure of the Zakarpatska oblast), which is presented in the form of the division into four groups. The spatial distribution of the territory and the NFR objects do not sufficiently meet the criteria of local representativeness, so their spatial structure needs significant improvement, be specific – the creation of nature reserves, especially in the lowlands of the region. The average density of nature protection objects in the region (36 units / 1000 km2 ) is almost three times higher than the corresponding indicator in the neighboring Lviv region. The average value of the reserve factor in the region makes 14.17 %. It has been found that the reserve ratio demonstrates geographically the largest disproportion in Zakarpatska oblast. It is the highest indicator in turns of administrative entities in the districts of Mizhhiria, Velyky Bereznyi and Rakhiv. The lowest one is in Svaliava and Berehove districts, respectively. In addition, the reserve ratio compared to the national average indicator and in other European countries has been carried out. The quality of the nature reserve network is determined by the insularity coefficient, which indicates the size of the NRF objects and their stability. Further expansion of the network of nature protection objects in Zakarpatska oblast is possible due to the creation of Latorytsa, Shaian and Uzhok landscape parks. A big assumption can be made that by 2020 it will be possible to create new and expand existing areas of NRF in the region up to 100–120 thousand hectares, which will increase the protected area up to 20–22 %. The key issues of nature reserves to be developed in Zakarpatska oblast are primarily related to the imperfection of the management system. To handle this problem, there is an urgent need to develop a strategy, which will envisage the perception of the NRF as a holistic anthropogenic and natural unit in order to put into practice the environmental, scientific, educational and recreational functions
Spatial analysis of natural reserve fund of the Zakarpatska Oblast
Keywords: nature reserve fund (NRF); reserve factor; index of insularization; Zakarpatska oblast; density of nature protection objects